Globalization, Transnational Corporations, the State and Democracy 37-48 - Bonanno, Alessandro (The International Journal of Sociology of Agriculture and Food, 2004)
In this article I argue that TNCs are the most powerful actors under globalization. Additionally, I contend that the contradictory relationship between TNCs and the state represents one of the most important aspects of this era. The core of this article, however, probes the issue of future outcomes of globalization. My point is that, while globalization is a response of the dominant groups to the gains and status that subordinate classes obtained under Fordism, it contains important contradictions that allow the possibility for the democratization of contemporary society. Under Fordism, subordinate classes’ gains established never-reached-before levels of substantive democracy. Globalization represents a dominant class’ response to this situation and, above all, an attack on labor and class based movements and the historical Left. Under globalization, the historical Left’s ability to organize and find strength in the factories and agricultural fields has been significantly diminished. Resistance emerged from new social movements. The environmental and consumer movements are two among these new social movements. Because of their focus on quality of life and consumption, they have the possibility to counter TNCs and establish substantive forms of democracy. My point is that these new social movements represent new emancipatory actors in the era of globalization. New emancipatory actors are accompanied by spaces of emancipation. I identify one of these spaces in the state. Because of its contradictory relationship with TNCs, the state is called to support and legitimize corporate actions in a situation in which TNCs tend to by-pass state demands and consequently limit the state’s ability to assist them. This situation opens up a crisis of legitimation in which the state is called to justify actions that it cannot fully control and regulate. I further argue that the contradiction of realization experienced by TNCs is another space of emancipatory action. I argue that TNCs’ need to realize their production – i.e., to sell the commodities they produce in order to transform them into money – makes them vulnerable to new social movements’ demands and create the possibility for more ethically and socially acceptable forms of production. I conclude the article by arguing that, in spite of the above mentioned contradictions and anti-corporate movements, TNCs remain firmly in control of contemporary society. This situation makes the attainment of more democratic conditions a contested terrain whose outcome will be decided by the ability of alternative forces to exploit globalization’s contradictions and use available spaces of emancipation.